Exploring the effects of e-waste on soil, water quality and human health - Laxmi Kant Bhardwaj; Prangya Rath; Harshita Jain; Moharana Choudhury (Discover Civil Engineering, 2025)
Abstract One of the fastest-growing waste streams globally, e-waste is a severe environmental and public health threat. India generates about 1.45 million metric tons of e-waste annually, and the recycling rate is approximately 5%. Rapid improvements in information and communication technology are forecast to continue exacerbating global e-waste production’s growth, projected to increase by 4–5% annually into the foreseeable future. Poor end-of-life management of e-waste results in the release of hazardous organic mixtures and heavy metals like lead (Pb) into the air, soil, and water, and poses significant health risks such as respiratory problems and cardiovascular disease. By critically examining e-waste management strategies, this review shows that sustainable policies are vital in reducing the observed risks. This review focuses on sustainable practices and proper legislation that can improve the overall e-waste impacts and their implications on human health and its surrounding environment. In addition, the review recommends the implementation of innovative recycling technologies and public awareness campaigns to boost recycling rates and public perception of e-waste hazards. This review synthesizes the practices and impacts of e-waste generation and comprehensively provides actionable insights for policy and stakeholder responses to address this crucial problem.